2018
DOI: 10.1186/s41182-018-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy of DuraNet® long-lasting insecticidal nets against wild populations of Anopheles arabiensis in experimental huts

Abstract: BackgroundMosquitoes have developed resistance to multiple classes of insecticides for malaria vector control. A new generation of long-lasting insecticidal bed nets (LLINs) has been developed with increased efficacy against these resistant mosquitoes. The present study therefore evaluated the efficacy of the pyrethroid-based LLINs, DuraNet versus PermaNet 3.0, in an Eastern Africa hut design in Magugu in northern Tanzania where mosquitoes’ population higher proportion (69.3%) has been identified as Anopheles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The positive control nets (DuraNet) had protective efficacy of 40.4% before washing, which dropped to 2.6% after 20 washes. This sharp decline on protection efficacy was contrary to the previous study [8]. The data gathered from India showed that MAGNet had the highest blood-feeding inhibition, ranging from 43.3 to 48.1%, which was comparatively better than that in Muheza [27]; the study conducted in M’bé, Côte d’Ivoire had feeding inhibition of 40% for MAGNet which is lower than the Tanzania and India sites [26].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The positive control nets (DuraNet) had protective efficacy of 40.4% before washing, which dropped to 2.6% after 20 washes. This sharp decline on protection efficacy was contrary to the previous study [8]. The data gathered from India showed that MAGNet had the highest blood-feeding inhibition, ranging from 43.3 to 48.1%, which was comparatively better than that in Muheza [27]; the study conducted in M’bé, Côte d’Ivoire had feeding inhibition of 40% for MAGNet which is lower than the Tanzania and India sites [26].…”
Section: Discussionmentioning
confidence: 74%
“…The low mortality of wild population of mosquitoes observed in the Muheza study site is suggested to be attributed to high resistance frequency observed in wild populations in previous findings [33, 34]. Due to the main effect of resistance, the most important measures of evaluated LLIN strength was recorded in terms of personal protection and killing effect outcomes [8, 35].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations